Gronwall's conjecture for 3-webs with two pencils of lines - Agafonov, Sergey I. [UNESP] (Elsevier, 2023)
We prove the old-standing Gronwall conjecture in the particular case of linear 3-webs whose 2 foliations are 2 pencils of lines. For a non-hexagonal 3-web, we also introduce a family of projective torsion-free Cartan connections, the web leaves being geodesics for each member of the family, and give a web linearization criterion.
Keywords: Cartan connection; Gronwall conjecture; Linear 3-web